Group of girls posing in costume - Unknown:::Creator::::::::::::
Negative shows a group of girls sitting or reclining in theatrical poses. The girl to the far right is drumming. All are in costumes, consisting of headresses, loose fitting clothing, and vambraces (metal or leather forearm guards). Standing on the far left is an adult woman, also in costume. They are outdoors, probably at the YWCA's Camp Ayun Mapu in Big Basin, California